Progression of experimental peri‐implantitis in guided bone regeneration and pristine bone: A preclinical in vivo study - Ko, Young‐Chang; Lee, Jungwon; Lee, Dongseob; Seol, Yang‐Jo; Koo, Ki‐Tae; Lee, Yong‐Moo (Journal of periodontology (1970), 2023)
Background Guided bone regeneration (GBR) is the most widely used technique for overcoming the deficiency of alveolar bone. However, the progression of peri‐implantitis in regenerative and pristine bone sites has not been fully investigated. The aim of this study is to compare experimental peri‐implantitis around implants placed in pristine bone and GBR sites. Methods Bilateral mandibular first molars were extracted from six beagle dogs, and standardized horizontal ridge defect was simultaneously created at predetermined site in unilateral mandible. After 8 weeks, guided bone regeneration procedure was conducted at the defect site. After 16 weeks, implants (ϕ 3.6×8.0 mm) were placed at both extracted sites. This study included 3 months of active breakdown and another 3 months of spontaneous progression period. Radiographs were taken at each phase and specimens were obtained for histological, immunohistochemical, and polarized light microscopic analysis. Results Marginal bone loss around implant did not show the significant differences between pristine bone and GBR sites during spontaneous progression period. In immunohistochemical analysis, inflammatory and immune‐related cells were predominantly detected in peri‐implantitis‒affected area rather than unaffected area. In the polarized light microscopic analysis, substantial reductions in the amount and thickness of collagen fibers were observed in peri‐implantitis‒affected area compared with unaffected tissues. However, there were no significant differences in histological, immunohistochemical, polarized light microscopic outcomes between pristine bone and GBR sites. Conclusion Previous hard tissue grafting at the implant sites did not affect experimental peri‐implantitis and exhibited similar radiographic, histological, immunohistochemical, and polarized light microscopic outcomes compared with those of pristine bone sites.